2019
DOI: 10.3390/w11071489
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Hydrological and Sedimentation Effects from Bottom Topography Change in a Complex River–Lake System of Poyang Lake, China

Abstract: In recent years, a dramatic decline in Poyang Lake water levels and a shrinking water surface have raised concerns about water security and the wetland ecosystem. Changes in bottom topography due to sand mining activities in the lake was supposed to be one of the influencing factors of these changes. In response to this issue, the current study analyzed the change of lake bottom topography from observed digital elevation model (DEM) data, and quantitatively assessed the spatial and temporal responses of lake h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…Previous studies have corroborated the effectiveness and robustness of back-propagation neural networks for modeling the water level of Poyang Lake (Li et al 2015;Ye et al 2019). In the original paper, Figs.…”
mentioning
confidence: 70%
“…Previous studies have corroborated the effectiveness and robustness of back-propagation neural networks for modeling the water level of Poyang Lake (Li et al 2015;Ye et al 2019). In the original paper, Figs.…”
mentioning
confidence: 70%
“…Therefore, the sediment deposition in these two lakes is probably more obvious compared to other lakes. Ye et al (2019) indicated a total volume of 0.096 Gt/yr sediment in a net change of lake bottom topography during 2000-2011, which did not suffer radical changes for Poyang Lake. Previous studies have also shown that Poyang Lake bathymetry in most areas is relatively stable, and the storage estimation bias caused by deposition processes is significantly less than 1% except for the dry season (Li Y. et al, 2020;Yuan et al, 2021).…”
Section: Discussionmentioning
confidence: 92%
“…River-bed stability and bank erosion Loss of productive cultivation areas [92,128] Food production Sediment deposition Loss of deep pools [129,130] Species diversity Impact on food webs [131,132] Species diversity Changes in sediment composition Impact on benthic communities [133] Species diversity Bathymetric changes Changes in water levels [134,135] Water availability…”
Section: Sand Miningmentioning
confidence: 99%